Lactate parameters and 100 m freestyle results in male and female youth swimmers - Thanopoulos, V.; Rozi, G.; Lampadari, V. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The aim of the present study was: a) the correlation between lactate parameters and lOOm freestyle results and b) differences between blood lactate recovery parameters between genders in youth swimmers. The sample of this study consisted of 20 swimmers, of them 10 were male of age=16±1 y, height 180±5 cm and mass70±8 kg and 10 were female of Age=16±0.5 y, height=168±7 cm and mass=59±5 kg. Subjects performed lOOm freestyle with maximum intensity (100VEL). Performance time was recorded and heart rate (HR) recorded after the test. For the determination of maximum accumulation of lactic acid (laMAX), blood capillary samples were taken in 3rd, 5th and 7th m in postexercise. The results of this study showed that there is statistical significant relationship between 100vEL and timecourse of blood lactate recovery parameters as predictor variables at R2 adi = 0.97, Standard Error = 0.68, p = 0.000. Statistically significant differences between male and female swimmers was only found at: t_laMAX- t=1.982, p=0.039 (347.4±72.4 vs 261.8±87.2 sec for male and female swimmers to reach Mac lactate, respectively).